2016
DOI: 10.1038/cddis.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of Caspase-3 predict favourable response to 5FU-based chemotherapy in advanced colorectal cancer: Caspase-3 inhibition as a therapeutic approach

Abstract: Colorectal cancer (CRC) is one of the most common cancers in the Western world. 5-Fluorouracil (5FU)-based chemotherapy (CT) remains the mainstay treatment of CRC in the advanced setting, and activates executioner caspases in target cells. Executioner caspases are key proteins involved in cell disassembly during apoptosis. Activation of executioner caspases also has a role in tissue regeneration and repopulation by stimulating signal transduction and cell proliferation in neighbouring, non-apoptotic cells as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 35 publications
5
59
0
2
Order By: Relevance
“…Similarly, a recent study [36] showed that DNLD, a specific caspase 3 inhibitor, significantly reduced chemotherapy induced COX-2 upregulation and PGE 2 release, corroborating that COX-2/PGE 2 axis acted as downstream effectors of caspase 3. In addition, our data also showed that inhibition of caspase 3 activity significantly reduced irradiation-induced VEGF-A secretion.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, a recent study [36] showed that DNLD, a specific caspase 3 inhibitor, significantly reduced chemotherapy induced COX-2 upregulation and PGE 2 release, corroborating that COX-2/PGE 2 axis acted as downstream effectors of caspase 3. In addition, our data also showed that inhibition of caspase 3 activity significantly reduced irradiation-induced VEGF-A secretion.…”
Section: Discussionmentioning
confidence: 54%
“…19 Several studies have shown that caspases are enzymes that are a member of the cysteine family, and are critical to the changes of morphological and biochemistry during apoptosis. 20,21 Caspase-3 is a main executioner caspases in cell and activated by pro-apoptotic signals, and has a key role in the terminal phase of apoptosis induced by diverse stimuli. 21,22 Our data demonstrated that Vglycin-induced apoptosis occurred by modification of Bax and Bcl-2 involved in the apoptotic mitochondrial pathway, and resulted in caspase-3 activation, which promotes apoptosis in CCCs.…”
mentioning
confidence: 99%
“…20,21 Caspase-3 is a main executioner caspases in cell and activated by pro-apoptotic signals, and has a key role in the terminal phase of apoptosis induced by diverse stimuli. 21,22 Our data demonstrated that Vglycin-induced apoptosis occurred by modification of Bax and Bcl-2 involved in the apoptotic mitochondrial pathway, and resulted in caspase-3 activation, which promotes apoptosis in CCCs. Specifically, Vglycin alters the Bax/Bcl-2 ratio and may trigger the apoptotic pathway in CCCs.…”
mentioning
confidence: 99%
“…Так, J. Alcaide et al (2013) [25], L. Flanagan et al (2016) [24] сообщали о том, что каспаза-3 может быть исполь-зована в качестве прогностического маркера, а высокий уровень экспрессии фермента апоптотической дегра-дации ассоциирован с плохим прогнозом для жизни больных колоректальной аденокарциномой. P. Noble et al (2015) [16] в своём исследовании пришли к иному вы-воду: высокий уровень экспрессии каспазы-3 клетками колоректальной аденокарциномы ассоциирован с благо-приятным прогнозом для жизни пациентов.…”
Section: таблицаunclassified
“…Полученные данные свидетельствуют о тесной ассо-циации процессов пролиферации и апоптоза клеток, формирующих паренхиму и строму колоректальной аденокарциномы. L. Flanagan et al (2016) сообщали об отсутствии корреляций между уровнями экспрессии Ki-67 и каспазы-3 опухолевыми клетками колорек-тального рака [24], в то время как вопрос о наличии корреляционных связей между уровнями экспрессии данных маркеров клетками паренхимы и стромы опу-холи не освещён в современной литературе.…”
Section: таблицаunclassified